Political connections and corporate financial decision making - Belghitar, Yacine; Clark, Ephraim; Saeed, Abubakr (Springer, 2018)
This paper investigates whether and how political connections influence managerial financial decisions. Our study reveals that those firms that have a politician on its board of directors are highly leveraged, use more long-term debt, hold large excess cash and are associated with low quality financial reporting compared to their non-connected counterparts. These effects escalate with the strength of the connected politician and whether he or his party is in power. The winning party effect is observed to be stronger than victory by the politician himself. Overall, our paper provides strong evidence that political connection is a two-edged sword. It is indeed a valuable resource for connected firms, but it comes at a cost of higher agency problems.
Keywords: Political connection; Earnings management; Financial policies; Emerging market